Evidence that eating baked egg or milk influences egg or milk allergy resolution: a systematic review. Issue 6 (17th May 2017) - Lambert, R.; Grimshaw, K. E. C.; Ellis, B.; Jaitly, J.; Roberts, G.
Summary: Background: It has been proposed that the frequent ingestion of baked hen's egg or cow's milk accelerates the resolution of hen's egg or cow's milk allergy. This practice is being introduced into clinical practice. Objective: To systematically review the evidence to determine whether the introduction of baked hen's egg or cow's milk into the diet of children with hen's egg or cow's milk allergies respectively leads to a larger proportion of children outgrowing these allergies than expected. Methods: A systematic review of the literature was conducted in Medline, Embase and CINAHL. The inclusion criteria were as follows: randomized control trials, case‐control or cohort studies; children aged 0–18 years with hen's egg or cow's milk allergy; baked hen's egg or cow's milk intervention with or without a comparator; and resolution of the hen's egg or cow's milk allergy as determined by food challenge as the outcome. Studies were critically appraised using the quality assessment tool for quantitative studies. PROSPERO reference CRD42015026029. Results: We identified 851 and 2816 hen's egg and cow's milk articles respectively. Only three hen's egg and three cow's milk studies fulfilled our pre‐specified inclusion criteria. The studies concluded that baked products either increased the likelihood of the resolution of allergy or accelerated resolution. However, when critiqued, all studies were classified as weak because they were observational, lacking an appropriate control group; this brings into doubt the study's conclusions. There were a number of examples of severe reactions to baked products. Conclusion: There is little evidence to address the hypothesis that the ingestion of baked hen's egg or cow's milk results in more patients outgrowing their hen's egg or cow's milk allergy respectively. Data are required from a trial comparing the resolution rates of baked‐tolerant participants who are randomized to ingest or avoid baked products to assess the accuracy of this hypothesis.